2002
DOI: 10.2960/j.v30.a1
|View full text |Cite
|
Sign up to set email alerts
|

The Feeding Ecology of Flatfish in the Northwest Atlantic

Abstract: Flatfish are an economically and ecologically important component of continental shelf ecosystems worldwide. These species are impacted from fishing activities, both as direct targets and through indirect effects on habitat and food supply. We examined 25 years of diet data for juveniles and adults of nine species of flatfish in the Northwest Atlantic on the continental shelf off of the USA and parts of Canada in order to understand how flatfish feeding ecology may have changed after decades of fishing and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 16 publications
7
49
1
6
Order By: Relevance
“…The diets of Summer Flounder, Weakfi sh, Bluefi sh, and Striped Bass on the inner continental shelf of New Jersey during summer varied month to monthan observation that could not be obtained from previous studies conducted in the region across a greater portion of the shelf region over multiple years (Garrison and Link, 2000b;Link et al, 2002;Walter et al, 2003;Buckel et al, 2009;Smith and Link, 2010). The fi ner scale in our study accounts for the slightly different patterns of similarity among Summer Flounder, Weakfi sh, Bluefi sh, and Striped Bass diets in comparison with results that had been reported previously for the shelf ecosystem of the northeastern United States (Garrison and Link, 2000b).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The diets of Summer Flounder, Weakfi sh, Bluefi sh, and Striped Bass on the inner continental shelf of New Jersey during summer varied month to monthan observation that could not be obtained from previous studies conducted in the region across a greater portion of the shelf region over multiple years (Garrison and Link, 2000b;Link et al, 2002;Walter et al, 2003;Buckel et al, 2009;Smith and Link, 2010). The fi ner scale in our study accounts for the slightly different patterns of similarity among Summer Flounder, Weakfi sh, Bluefi sh, and Striped Bass diets in comparison with results that had been reported previously for the shelf ecosystem of the northeastern United States (Garrison and Link, 2000b).…”
Section: Discussionmentioning
confidence: 65%
“…These species co-occur seasonally and feed on similar prey, indicating potential for competitive interactions. However, studies of food habits for these species generally have focused on estuarine collections (Gartland et al, 2006;Latour et al, 2008) or have been limited to seasonal, offshore (at depths of 5-400 m) collections aggregated over multiple years (Buckel et al, 1999b, Garrison and Link, 2000a, 2000bLink et al, 2002;Overton et al, 2008;. Further, most prior studies on these species typically have focused on a single (Gartland et al, 2006;Latour et al, 2008) or a pair of species (Buckel and McKown, 2002;Buckel et al, 2009).…”
mentioning
confidence: 99%
“…1) is assumed to be high quality habitat based on the consistently high numbers of yellowtail flounder found there. Yellowtail flounder eggs, larvae, juveniles, and adults are all found in this area (Johnson et al 1999); it has the sandy substrate (Almeida et al 2005, Kostylev et al 2005, Link et al 2005) and food items that yellowtails prefer (Johnson et al 1999, Link et al 2002. Tagging studies also indicate limited movements of yellowtails out of this area (Stone & Nelson 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Link et al (2005) also showed that the low energy habitat contained greater abundance and diversity of benthic invertebrates than the high energy habitat. This would seem to indicate higher food availability since yellowtail flounder eat primarily polychaetes and small crustaceans (Langton 1983, Link et al 2002. These habitats appear to continue into 5Z, the closed area on the Canadian side of the border (Kostylev et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because they are often the dominant marine benthic fauna in shallow waters, they are considered to be a key group in coastal food webs (Takahashi et al 1999). Mysids have been reported to be one of the main prey organisms of many juvenile fish and carnivorous crustaceans in coastal areas , Link et al 2002, Stergiou & Karpouzi 2002, Nakane et al 2011, and to play an important role in the transport of primary products to organisms at higher trophic levels.…”
Section: Introductionmentioning
confidence: 99%